Typology of Idiomatic Expressions in the Dialogue of Chapter One of “Harry Potter and the Chamber of Secrets” - Faras Embun Dini; Arifuddin Arifuddin; Boniesta Zulandha Melani (Journal of English Education Forum (JEEF), 2026)
This study aims to analyze idiomatic expressions found in the dialogue of Chapter One of Harry Potter and the Chamber of Secrets. The objectives are to identify the idiomatic expressions, classify them based on Fernando’s (1996) typology, and analyze their contextual meanings and functions in dialogue. This study employs a descriptive qualitative method using dialogue excerpts from the selected chapter as the data source. The findings reveal that there are eleven idiomatic expressions identified in the dialogue, consisting of two pure idioms, seven semi-idioms, and two literal idioms. Semi-idioms are the most dominant type, reflecting a balance between literal and figurative meaning in everyday conversational contexts. The findings also show that interpretation of idiomatic meaning depends heavily on contextual factors, including the surrounding dialogue, narrative information, situational circumstances, and interpersonal relationships between the characters. In addition, the analysis demonstrates that idiomatic expressions serve various functions in the dialogue, including expressing authority, conveying evaluation and personal attitudes, managing interpersonal relationships, and influencing the psychological responses of other characters. The findings suggest that idiomatic expressions are not used randomly, but also closely related to the communicative needs of the characters and the interactional contexts in which they occur.